Changing policies over timber supply and its potential impacts to the furniture industries of Jepara, Indonesia - Dodik Ridho Nurrochmat; Efi Yuliati Yovi; Oki Hadiyati; Muhammad Sidiq; James Thomas Erbaugh (Jurnal Manajemen Hutan Tropika, 2015)
Though some scholars argue that Indonesian wood furniture industries are in decline, these industries remain a driving force for regional and national economies. Indonesian wood furniture has a long value chain, including: forest farmers, log traders, artisans, and furniture outlets. In Jepara, Central Java, wood furniture industries contain significant regional and historical importance. Jeparanese wood furniture industries demonstrated great resilience during the economic crisis in the late nineties. Although they were previously able to withstand the pressures of economic crisis, the enactment of Minister of Forestry Regulation (MoFor Reg.) 7/2009 on wood allocation for local use -as one of the implementing regulation of decentralization law 32/2004- causes a potential reduction of wood supply to Jepara. Since September 30th, 2014, however, the constellation of domestic timber politics has changed due to the new decentralization law (23/2014), which shifted most regulations on forest and forest products from the regency to the province. This study evaluates the dynamics of decentralization policy on timber allocation and examines the power of different stakeholders given the changing regulation and its consequences for Jeparanese wood production.